Biological control of the Genus Hyalomma (Hyalomma anatolicum) by using entomopathogenic indigenous fungi (Beauveria bassiana). - Mustafa, Bahzad; Hemn Ahmed Hama Ali (University of Thi-Qar Journal of agricultural research, 2025)
A total of 1147 ticks were collected from 360 suspected cattle across three ecological zones to evaluate and compare the efficacy of biological and chemical methods against hard ticks (genus: Hyalomma), which are the highest infesting ticks on cattle in Sulaymaniyah, Iraq. Focused on three developmental stages-larvae, nymphs, and adults-they are tested with both synthetic (chemical) acaricides and entomopathogenic fungus (Beauveria bassiana). Biological control trials involved spraying Beauveria bassiana spores at three concentrations: 10^6, 10^7, and 10^8 spores/ml. The fungus preparation was applied directly to ticks at different life stages, and mortality rates were monitored. LT50 and LT90 values were calculated for each combination, showing higher mortality and faster lethal time at higher concentrations. Another test using commercial acaricides was conducted under the same experimental conditions, and the results showed that the chemical treatment at a concentration of 2.5% deltamethrin caused higher initial mortality, while the fungal treatment showed progressive and lasting effects, particularly at the adult stage and at higher spore concentrations. Overall, the study concludes that Beauveria bassiana is a promising biocontrol agent that, when properly formulated, can serve as an eco-friendly alternative to chemical acaricides in integrated tick management strategies in livestock systems.